USING CHAIN CARD GAME TO IMPROVE THE WRITING SKILL OF THE SIXTH GRADE SD KARTIKA IV-1 MALANG - Iflinda Virgina Sutalistya (UIBU, 2018)
Based on the implementation of Class Action Research (CAR) by using strategy of chain card game, there are detailed description for each cycle. In cycle I the students who has mastered the learning progress achieve 60% with the score average is 73,3. For the learning activities there is 2 complete descriptors with the percentage of 85% and 3 incomplete descriptors with the percentage of 47,8%. For creativity there are 2 complete descriptors with the percentage of 85% and 2 incomplete descriptors with the percentage of 55%. For the Students’ pleasant all off the descriptors are complete with the percentage of 93,3%. The interactivity of the students show that all the descriptors are complete with the percentage of 85,5%. There is an increasing of score that achieved by students who has mastered the learning. That is 80% with the average is 81,0. For the learning activities all of the descriptors are complete with the percentage of 94%. There is an increasing of 9,0%. For the interactivity all of the descriptors are complete with percentage of 89,1%. There is an increasing of 4,1%. For the students’ pleasant 100% are the descriptors are complete. There is an increasing of 6,7%. For Interactivity, all of the descriptors also complete with the percentage of 96,7%. There is an increasing of 11,2%. Considering the data above, the implementation of chain card game can improve the students writing skill of sixth grade at SD Kartika IV-1 Malang